Developing and Evaluating an Explainable Deep Learning–Based User Interface for Libyan Currency Authentication. - Masoud Mohammed, Mohammed; .I.G.Masbah, Aeman; M. Elmansori, Mansaf (Scientific Journal of University of Benghazi, 2025)
The problem of counterfeit currency production and distribution is increasing, driven by technological advancements, particularly the development of advanced printing machines. The ongoing issue of counterfeit currency poses a significant threat to the national economy, necessitating the creation of an effective detection system. In light of this problem, this study proposes an intelligent system for identifying and detecting counterfeit Libyan currency. This system relies on deep learning techniques. Our proposed model is based on the EfficientNet-B4 controlled architecture, which seeks to optimize computing power and accuracy. In this study, the dataset was prepared and preprocessed using Gaussian filtering to reduce noise and normalize. The general framework developed here consists of two stages: The first stage is an intelligent filter that attempts to exclude any banknotes or images that are not Libyan currency, ensuring that only data related to Libyan banknotes is transmitted to the second stage of the model. The second stage is the core of the study, as it will determine whether Libyan currency is authentic or counterfeit. To improve the transparency of the model and enhance the understanding of its results, Grad-CAM software was used to generate heat maps that clearly show the banknote regions that contributed most to the model’s decision-making. To demonstrate the system’s usability, a mock-up user interface was designed to illustrate the system’s analysis and provide a practical environment. The results demonstrated good classification performance, consistently exceeding 90%, demonstrating how the proposed approach can be effectively applied to these models in practical situations. The findings of this research provide a practical framework to help financial institutions mitigate counterfeiting as part of the relevant compliance objectives that will determine the security of the monetary system. KEYWORDS: , , , ,